Rekonstruksi Metode Penafsiran Ayat Mutasyâbih Lafẓî (Ayat Beredaksi Mirip) Berbasis Teori Munâsabah Al-Âyât - Agus Imam Kharomen (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2023)
This article is a response to the method of interpretation (tafsîr) of identical versesof Nashruddin Baidan (b. 1951 M) which has not succeeded in revealing the meaning of the verse mutasyâbih lafẓî totally as the result of interpretation is still limited to the meaning behind the different text (redaction). This study is a library-based research, with the object of study of Nashruddin Baidan method of tafsîr, by using descriptive-analytic methods, through content analysis and interpretation approaches, as well as the theory of 'Ulûm al-Qur`ân and the rules of interpretation. The literatures used include Metode Penafsiran al-Qur’an: Kajian Kritis terhadap Ayat-ayat Beredaksi Mirip by Nashruddin Baidan (b. 1951 M), al-Burhân fî ‘Ulûm al- Qur`ân by al-Zarkasyî (d. 1392 M), Kaidah Tafsir by M. Quraish Shihab (b. 1944 M), Durrah al-Tanzîl wa Ghurrah al-Ta’wîl by al-Iskâfî (d. 1029 M), al-Baḥr al-Muḥîṭ by Abû Ḥayyân (d. 1344 M) and al-Taḥrîr wa al-Tanwîr by Ibnu ‘Âsyûr (d. 1973 M). This study shows the importance of examiningthe meaning relationship among the mutasyâbih lafẓî verses. This study proves that munâsabah can be an approach to reveal the meaning relationship among mutasyâbih lafẓî verses so that a comprehensive meaning of the verse can beobtained.